Variations of the femoral artery position in relation to femoral vein and mid-inguinal point: a cadaveric study - Taib, Che Norma Mat; Nasir, Aina Amira Mohamad; Ahmad, Nurul Arina; Moklas, Mohamad Aris Mohd (Universiti Putra Malaysia Press, 2023)
Introduction: Femoral artery is one of the major arteries in human body. It is more preference for catheterization in some medical procedures. This study was designed to identify anatomical variations of the femoral artery position, in relation to femoral vein and mid-inguinal point of human cadavers. Methods: Dissection was performed on 22 cadavers. The associations were analyzed using Fisher’s Exact test and correlation test. Results: There was superolateral positioning detected. Distal traversing was only observed on the left thigh. Bivariate analysis showed that there was a significant association of distance from anterior superior iliac spine (ASIS) to femoral artery between the right and left thigh. However, there was no significant association of distance from mid-inguinal point (MIP) to femoral artery between the right and left thigh, position of femoral artery to MIP between the right and left thigh and distance of traversing point between the right and left thigh. Conclusion: This study showed that distance from ASIS to mid-point of femoral artery was significantly associated with the left-right sided of cadavers, while distance from MIP to femoral artery, position of femoral artery to MIP and distance of traversing point were not significantly associated with the left-right sided of cadavers. These informations may help in diagnostic cardiac catheterization procedures and coronary interventions. Malaysian Journal of Medicine and Health Sciences (2023) 19(SUPP12): 1-6.